Targeting Histone Methylation in Cancer. Issue 5 (September 2017) - McCabe, Michael T.; Mohammad, Helai P.; Barbash, Olena; Kruger, Ryan G.
Abstract : Abstract: Most, if not all, human cancers exhibit altered epigenetic signatures that promote aberrant gene expression that contributes to cellular transformation. Historically, attempts to pharmacologically intervene in this process have focused on DNA methylation and histone acetylation. More recently, genome-wide studies have identified histone and chromatin regulators as one of the most frequently dysregulated functional classes in a wide range of cancer types. These findings have provided numerous potential therapeutic targets including many that affect histone methylation. These include histone lysine methyltransferases such as enhancer of zeste homolog 2 and DOT1L, protein arginine methyltransferases such as protein arginine methyltransferase 5, and histone lysine demethylases such as lysine-specific demethylase 1. This review presents the rationale for targeting histone methylation in oncology and provides an update on a few key targets that are being investigated in the clinic.